Encouraging young adults with a disability to be independent in their journey to work: A segmentation and application of Theory of Planned Behaviour approach - Beatson, Amanda (Heliyon, 2020)
This study investigates how young adults with disabilities can be encouraged to be independent in their travel to work and thus, transition more smoothly into the workforce. Using cluster analysis, we identify three segment groups of young adults with physical disabilities. The Theory of Planned Behaviour is then applied to examine differences and identify strategies that could provide assistance and support to these groups of workers in their travel to work. This study is the first to segment this group of workers and identify strategies to mitigate the often-unique challenges they face in their physical journey to work.